Does maxillary protraction with Alt-RAMEC protocol affect inferior sclera exposure? A controlled 3dMD study - ÖNEM ÖZBİLEN, ELVAN; ACAR, YASEMİN BAHAR; YILMAZ, HANİFE NURAY (My University, 2022)
Objective: The purpose of this controlled retrospective study was to measure and evaluate the inferior sclera exposure changes using 3dMD stereophotogrammetric images in a prepubertal Class III patient sample that underwent maxillary protraction with alternate rapid maxillary expansions and constrictions protocol followed by facemask. Methods: The study group included 15 prepubertal patients (mean age: 9.85 ± 1.44 years) with Class III malocclusion due to maxillary retrognathism. Nine weeks of alternate rapid maxillary expansions and constrictions protocol was followed prior to 7 months of face mask treatment and 3 months of retention with Bionator. Pretreatment (T0) and post-retention (T1) lateral cephalometric radiographs and 3dMD images were retrieved from clinical archive. The same records were used for a control group of 15 well-matched, untreated patients (mean age: 9.4 ± 0.79 years). The distance between the upper eyelid margin and the lower eyelid margin was recorded as the overall eye height (E), and the distance between inferior limbus and the lower eyelid margin was recorded as inferior sclera exposure (S). The S : E ratio in percentage was calculated. Sella-nasion-A point angle (SNA) was used as the skeletal variable. Results: SNA angle, right S : E, and left S : E changed significantly in both groups at T1-T0. The intergroup comparison was highly significant for SNA angle but was not significant for right and left S : E variables. Conclusion: The S : E ratio decreased significantly in both alternate rapid maxillary expansions and constrictions/facemask and the control groups. However, the change in S : E ratio between groups was not significant.
Keywords: DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Alt-RAMEC; Angle Class III; maxillary retrusion; sclera; stereophotogrammetry; REPETITIVE WEEKLY PROTOCOL; CLASS-III MALOCCLUSION; CLEFT PATIENTS; EXPANSION; COMPONENTS; FACEMASK; SKELETAL; SHOW; Alt-RAMEC; Angle Class III; maxillary retrusion; sclera; stereophotogrammetry